Etiopia : nälkä pois Etiopiasta, kampanja 85 (Etiopia Solidaarisuustili, 1985)
Mountain chain resembling a person's profile with mouth open, drop falling down into it; photograph of dry soil on the bottom Poster advertising campaign against hunger in Ethiopia PO-0170